العوامل المؤثرة على البطالة في سورية خلال الفترة 2001 – 2011 - عكروش محمد; شريقي مدى; ديوب أكرم (Latakia University Journal - Economic and Legal Sciences Series, 2018)
تعتبر مشكلة البطالة من المشاكل الأساسية التي يعاني منها المجتمع السوري، على الرغم من سعيها إلى التنمية الاقتصادية الاجتماعية إلا إنها ما زالت تشكل أكبر التحديات التي تواجه الاقتصاد السوري، وهدف البحث معرفة أثر العوامل المؤثرة على حجم البطالة في سورية ومنها ] حجم السكان الإجمالي،حجم السكان في سن العمل، بطالة الشباب في سن العمل ]15– 24[، الناتج المحلي الإجمالي نصيب الفرد من الناتج المحلي الإجمالي، الدخل الشهري، خلال الفترة 2011-2001، ومعرفة درجة تفسيرها لمشكلة البطالة، وكيف ترتبط تلك المتغيرات مع متغير البطالة من جهة، ومع بعضها البعض من جهة أخرى. وسيتم استخدام المنهج الوصفي في تفسير البيانات، كما اعتمد هذا البحث على المنهج التحليلي الإحصائي لمعرفة المتغيرات الأكثر ارتباطاً بمشكلة البطالة. أهم النتائج : زيادة عدد المتعطلين خلال الفترة المدروسة (58.6%)، الفجوة الجندرية لعدد المتعطلين عن العمل لصالح الذكور في الأعوام كافة، توجد علاقة ارتباط قوية جدا ً بين حجم البطالة ومعدل بطالة الشباب، علاقة الارتباط ضعيفة جداً وغير دالة إحصائيا بين حجم البطالة وباقي العوامل باستثناء بطالة الشباب يوجد علاقة ارتباط قوية بين حجم البطالة وباقي المتغيرات. Considered the problem of unemployment of the basic problems of the Syrian society, despite the pursuit of socio-economic development, but it was still pose the biggest challenges facing the Syrian economy, The objective of this research to know the impact of factors affecting the volume of unemployment in Syria, including the size of the population overall, the size of the working age population, youth unemployment in the working-age[ 15-24 ], GDP per capita GDP, monthly income, during the period 2011 -2001, find out the degree of interpretation to the problem of unemployment and how these variables are associated with variable unemployment on the one hand, and with each other on the other. And it will use the descriptive approach in interpreting the data, as the adopted research on statistical analytical method to determine the most relevant to the problem of unemployment variables. The most important results: increasing the number of the unemployed during the period studied (58.6%), the gap of gender to the number of the unemployed in favor of males in the years of all, there is a very strong correlation between the size of unemployment and the rate of youth unemployment is a relationship, a very weak and function correlation statistically between the size of unemployment and the rest factors except youth unemployment there is a strong correlation between the size of unemployment and other variables relationship.